Industry-specific prevalence and gender disparity of common mental health problems in the UK: A national repetitive cross-sectional study - Shanquan Chen; Yuqi Wang (Frontiers Media S.A., 2023)
AimsThe aim of the study was to evaluate the prevalence and temporal trend of common mental health problems (CMHPs) in the UK by industrial classification from 2012-2014 to 2016-2018 while evaluating the corresponding gender disparities.MethodsWe used data from the Health Survey for England. CMPH was judged by a 12-item General Health Questionnaire. Industrial classifications were defined using the UK Standard Industrial Classification of Economic Activities. Data were fitted by the logistic models.ResultsIn this study, 19,581 participants covering 20 industries were included. In total, 18.8% of participants screened positive for CMHP in 2016-2018, which significantly increased from 16.0% in 2012-2014 [adjusted OR (AOR) = 1.17, 95% CI 1.08-1.27]. In 2016-2018, the prevalence of CMHP ranged from 6.2% in the industry of mining and quarrying to 23.8% in the industry of accommodation and food service activities. From 2012-2014 to 2016-2018, none of the 20 industries studied experienced significant decreases in the above prevalence; conversely, three industries saw significant increases, including wholesale and retail trade, repair of motor vehicles and motorcycles (AOR for trend = 1.32, 95% CI 1.04-1.67), construction (AOR for trend = 1.66, 95% CI 1.23-2.24), and other service activities, which cannot be classified (AOR for trend = 1.94, 95% CI 1.06-3.55). In total, 11 of the 20 industries studied had significant gender disparities against women, with the smallest gap being in the industry of transport and storage (AOR = 1.47, 95% CI 1.09-2.0) and the highest in the industry of arts, entertainment, and recreation (AOR = 6.19, 95% CI 2.94-13.03). From 2012-2014 to 2016-2018, gender disparities were narrowed only in two industries, including human health and social work activities (AOR for trend = 0.45, 95% CI 0.27-0.74), and transport and storage (AOR for trend = 0.5, 95% CI 0.27-0.91).ConclusionThe prevalence of CMHPs has increased and had a wide variation across industries in the UK. There were disparities against women, and the gender disparities have been keeping almost no improvement from 2012-2014 to 2016-2018.